Maximal oxygen uptake, total metabolic energy expenditure, and energy cost in swimmers with physical disabilities - Feitosa, W. G.; Barbosa, T. M.; Correia, R. D. A.; Castro, F. A. D. S. (International Journal of Performance Analysis in Sport, 2019)
The purpose of this study was to assess the maximum oxygen uptake (VO2max), the total metabolic energy expenditure (Etot), and the energy cost (C) measured as the speed of VO2max in swimmers with physical impairments. Eleven swimmers performed an Nx200-m front crawl test from a low to all-out speed and data were obtained at maximum aerobic power. The oxygen uptake was measured breath-by-breath by a telemetric gas exchange system. The Etot was calculated from the aerobic and anaerobic pathways at maximal intensity. The C was obtained by the ratio of the Etot and the mean swimming speed. The VO2max was 38.2 ± 8.3 mL/kg/min, the Etot was 191.9 ± 51.7 kJ, and the C was 0.8 ± 0.2 kJ/m. The energy contribution of the aerobic pathway was higher (p < 0.001) than that of both the anaerobic pathways, which were similar (p > 0.05). There was no gender effect on the results of the energy contributions (p > 0.05). The anaerobic lactic pathway contribution was higher in male than in female swimmers (p < 0.05). The VO2max and C were higher in swimmers who were less affected by physical impairment. The energy contribution of the aerobic pathways was similar for males and females.